Cognitive Flexibility in Schoolchild Through the Graphic Representation of Movement - Urraca-Martínez, MᵃLuz; Sastre-Riba, Sylvia (Frontiers in Psychology, 2021)
Neuroconstructivism postulates the progressive complexity of mental representation over the course of cognitive development and the role of the graphic representation of movement in the transformation of mental schemas, cognitive flexibility, and representational complexity. This study aims to: 1) understand children’s resources in the drawing of movement (5 to 8 years); and 2) verify whether there are differences in the graphic representation of movement as an indicator of cognitive flexibility. The participants were N=240 children aged 5 to 8 years; 1,440 drawings were collected representing 2,880 characters (both animate and inanimate) from six stories. The analysis consisted: 1) data quality control, using the kappa coefficient, and Generalizability Theory (GT) to test the instrument’s validity and reliability; 2) Multivariate General Analysis and Mixed Linear Analysis of the factors (age and stories); 3) Multivariate General Analysis of the graphic components: categories and microcategories, as well as the elements that make up the macrocategories: “Static”, ”Indication”, and “Movement”; and 4) calculation of the generalizability coefficient (G-coefficient). The results show that: a) age best explains variability, with a high effect size (η2=.732) across all components (F=153.445; p<.001), thus increasing its complexity; and b) at ages 6 and 7, “Indication” appears as a modulator of “Static” (age 5) toward “Movement” (age 8). The generalizability coefficient is optimal (.995). It is concluded that changes in the initial graphic representation of movement may interactively transform mental representation, thus increasing cognitive flexibility and prompting teaching applications to optimize such changes.